(3GdEbfGY aj GdbQGAGJ GdSHYs - (3GHf GdHGPT , CMeO Hf Ydj Hf CMeO Hf Nda GdCfUGQj GdZQfGWj, CHh LYaQ,J (B540 (3g` s
(3ChdgG (B:s
(3bG GdCSJGP GdCLd CHhLYaQ CMeO Hf Ydj GdeQF (B: (3GdMeO ddg GdPj de jLeY GdYde dEfSGf hdG bUQg Ydi ecGf , hdG MUQg HReGf s
(3BNQgG (B:s
(3Yf bJGOI Yf CfS Hf eGdc, Yf GdfHj Udi Gddg Ydjg hSde , bGd(B: (3eY cd NJeI OYhI eSJLGHI s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3gfGc ENJdGa aj GdJQbje fJjLI GdNWC aj JLdjO GdcJGH ahVYJ UaMI (B23 (3ecGf (B21 (3hgfGc HJQ Hjf (B42 (3h (B43 (3, hHjf (B64 (3,(B65 (3, Hjf (B84 (3, (B85s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs